Using The Mirror Story to Understand Self. Issue 1 (2nd January 2017) - Warren, Jane A.; Trujillo, Natasha P.; Asfaw, Amanuel H.; McKim, Courtney; Stoffers, Lindsay; Faimon, Kristina
ABSTRACT: Research indicates self-esteem reflects many factors in a person's life, such as relationships with parents or parent figures, attachment types, experiences of worth enhancement, ethnicity, generation, and cultural values. However, debate continues on whether self-esteem is simply a reflection of Western culture and may not be a universal factor of human nature. This research was undertaken to understand how four persons of diverse ethnic, gender, and age categories may each perceive the self from reading the same story. First, the authors offer a brief overview of how self-esteem is viewed and explore a few cultural, gender and age aspects of self-esteem. They then present our pilot study with the methodology, results, and discussion, and offer implications for mental health counselors.